2021
DOI: 10.29359/bjhpa.2021.suppl.1.05
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived health outcomes of recreation, exercise dependence, and life satisfaction: A study with fitness center members

Abstract: Background: This study aimed to investigate the relationship between perceived health outcomes of recreation, exercise dependence, and life satisfaction among fitness center members. Material and methods: The study sample consisted of 490 participants, 336 males, and 154 females, who were members of a private fitness center in Istanbul. The participants were selected using a purposeful sampling method. Data collection tools included the Perceived Health Outcomes of Recreation Scale, developed by Gomez et al. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Similar to the current study, Tükel and Temel (2020) reported no significant difference in terms of gender variable in LSS in their study. When the literature is considered, there are studies indicating significant differences in LSS in favor of male participants (Serdar, 2021). On the other hand, when the literature is reviewed for LIS, Demirel (2019) revealed results that support the results of the current study and reported that there is no significant difference in terms of gender variable in their study.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to the current study, Tükel and Temel (2020) reported no significant difference in terms of gender variable in LSS in their study. When the literature is considered, there are studies indicating significant differences in LSS in favor of male participants (Serdar, 2021). On the other hand, when the literature is reviewed for LIS, Demirel (2019) revealed results that support the results of the current study and reported that there is no significant difference in terms of gender variable in their study.…”
Section: Discussionsupporting
confidence: 82%
“…( 7 13 ). Some of the studies did not find a significant difference between the sub-dimensions of PHORS based on gender ( 7 11 ), marital status ( 8 10 ), sexual orientation and age ( 7 ), ethnicity ( 8 ), membership ( 9 13 ), activity type ( 9 ) and regional ( 13 ). Others reveal that there is a significant difference in PHORS scores based on income level and activity type ( 12 ), gender and age ( 13 ).…”
Section: Introductionmentioning
confidence: 99%